DIAGNOSIS OF FELINE PANLEUKOPENIA IN A MIXDOM CAT USING RAPID TEST AND HEMATOLOGY - Abdillah Moriffilos Rizaluddin,; Rell, Fedri; Andi Magfira Satya Apada,; Muhammad Fadhullah Mursalim,; Abdul Wahid Jamaluddin,; Yusuf, Baso (Buletin Veteriner Udayana, 2024)
Feline panleukopenia is a viral disease that often causes death in infected cats. This disease is caused by a single-stranded DNA virus called feline parvovirus. The examination was carried out to determine feline panleukopenia virus infection in cat. On Wednesday, October 25’ 2023, a 6-month-old male mixdom cat named Goldi was examined at the Hasanuddin University Teaching Veterinary Hospital. Based on information from the owner, the cat was vomiting, had bloody diarrhea and did not want to eat. The patient has never been vaccinated or given worm medicine. Physical examination found that the cat was very weak due to not wanting to eat and dehydration, heart rate 120/minute, respiratory rate 40 times/minute, conjunctiva pale and Capillary Refill Time: 2. Hematological examination of the blood found changes in parameters, namely leukopenia, lymphopenia, granulocytopenia and the mean corpuscular hemoglobin was low and the results of the rapid test showed 2 bands indicating the presence of FPV antigen in the goldi patient's feces. Based on clinical symptoms, disease history, results of physical examination, hematology and rapid tests, the mixdom cat named Goldi was diagnosed as infected with feline panleukopenia. Treatment is by administering 0.9% NaCL infusion, Metronidazole® antibiotics, Guanstrep® gastric antiulcer. Severe dehydration caused the goldi cat's life to fail so it was handed over to the owner to be buried. It is recommended to owners to clean cat feces because it can act as a carrier of the feline panleukopenia virus.